2015
DOI: 10.1245/s10434-015-4437-z
|View full text |Cite
|
Sign up to set email alerts
|

Active Surveillance for Adverse Events Within 90 Days: The Standard for Reporting Surgical Outcomes After Pancreatectomy

Abstract: Approximately one-third of severe adverse events and readmissions are reported more than 30 days after surgery. All adverse events that occur within 90 days of surgery must be identified and reported for accurate characterization of the morbidity associated with pancreatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…Regarding the delay in postoperative surveillance, Mise et al reported that 90‐day overall mortality significantly increased the morbidity rate compared to 30‐day mortality, and better represented mortality related to surgical procedures. Recent studies also suggested that 90‐day surveillance should be mandatory after major surgical procedures in order to better define postoperative complications . Regarding the classification, we used the NCI‐CTCAE classification, which includes more medical complications than the surgical classification.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the delay in postoperative surveillance, Mise et al reported that 90‐day overall mortality significantly increased the morbidity rate compared to 30‐day mortality, and better represented mortality related to surgical procedures. Recent studies also suggested that 90‐day surveillance should be mandatory after major surgical procedures in order to better define postoperative complications . Regarding the classification, we used the NCI‐CTCAE classification, which includes more medical complications than the surgical classification.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rapid access to potential radical resection is of fundamental importance for this pathology. However, despite the recent optimization of peri-operative optimization protocols, surgical techniques and anesthesiological treatments, morbidity and mortality after pancreatic resections are still not negligible especially in the case of cephalic localization [75]. In addition, patients with surgical resection are likely to require postoperative treatment in intensive care units, mainly reserved for COVID patients during the pandemic.…”
Section: Guidelines/recommendation For Pancreatic Cancermentioning
confidence: 99%
“…Surveillance for AEs was performed for at least 90 postoperative days by a single advanced practice nurse [3]. All new and existing AEs and associated supporting documentation were audited weekly for 90 d by the attending surgeon to validate, grade, and update the severity of the event using the modified Accordion system [11].…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Many AEs that develop within the hospital may resolve before discharge if managed appropriately. However, new AEs may occur and preexisting AEs may evolve after discharge [3]. These barriers to recovery may reduce postoperative quality of life, delay receipt of adjuvant therapy, and impair therapeutic outcomes of patients undergoing complex surgical procedures for cancer [4].…”
Section: Introductionmentioning
confidence: 99%